2019
DOI: 10.1001/jamaophthalmol.2019.2907
|View full text |Cite
|
Sign up to set email alerts
|

Why Don’t Yellow Night Vision Glasses Work?

Abstract: Over the years, two things have happened that make night driving increasingly difficult for me: I have grown old and automobile headlights have grown whiter and brighter. With the transition from kerosene carriage lamps to sealed beam incandescent and, more recently, high-intensity discharge and light-emitting diode (LED) headlamps, the color and brightness of headlights have gradually evolved from a pleasant and romantic yellow candlelight to a light as harsh, glaring, and painful as the sun is to me. So, if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The distortion reported by patients with disciform AMD and illustrated here has been interpreted by Massof 9 to suggest a perceptual closure of visual space around the scotoma analogous to the closure of a drawstring bag. This drawstring closure hypothesis is similar but not identical to our scotoma carving.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The distortion reported by patients with disciform AMD and illustrated here has been interpreted by Massof 9 to suggest a perceptual closure of visual space around the scotoma analogous to the closure of a drawstring bag. This drawstring closure hypothesis is similar but not identical to our scotoma carving.…”
Section: Discussionmentioning
confidence: 59%
“…In particular, the cause and nature of the distortions outside the scotoma are different in nature in these two cases. The reports of these spatial distortions surrounding AMD central scotomas led to the design of field remapping vision aids using counter distortions 9,69–72 . These authors proposed that the distortion introduced around the scotomas may be fully or largely compensated by a remapping image processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased levels of retinal straylight in the eye cause drivers to experience disability glare, which can be particularly problematic when driving at night (Van den Berg et al 2009). Some researchers have suggested that yellow-tinted lenses can reduce disability glare (Hammond et al 2009;Massof 2019). This hypothesis is often based on the assumption that the human eye is affected by Rayleigh-type light scattering, in which short-wavelength light is scattered more than medium-and long-wavelength lights.…”
mentioning
confidence: 99%